MUSICAL INSTRUMENT RENTAL SYSTEM AND SOUND SYSTEM IN THE STUDIO WITH THE MUSICAL 48 MICROSOFT VISUAL BASIC 6.0 - Dwi Suci Annisa (Jurnal Sistem Informasi, 2009)
Rental of musical instruments and sound system in Music Studio 48 is still done manually so that based on the analysis will be needed to create a computer-based administration system in accordance with the needs and desires of the leadership, especially in the case of rental of equipment, receipt of payment, and reports. Analysis at 48 Music Studio is through the documents and direct interviews with relevant parties to obtain accurate data. The menu is presented properly designed and adjusted to the leadership desires. Starting from design input to output leasing process so as to form a report in accordance with accounting theory. This strongly supports the readiness of companies in the future when developing and audited by the auditors.Recording process is still done manually, requiring a longer time compared to using computer technology.